2019
DOI: 10.1108/ijesm-11-2017-0005
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between renewable energy consumption and economic growth

Abstract: Purpose The purpose of this study is to investigate the relationship between renewable energy and economic growth of Bulgaria. Design/methodology/approach This study analyzes the relationship between renewable energy and economic growth of Bulgaria for the period 1990-2016, based on annual data, by using the Toda–Yamamoto analysis and Autogressive Distrubuted Lag (ARDL) bound test. This period is characterized by the democratization of the Balkans and several crisis cycles in Bulgaria. Renewable energy consu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(45 citation statements)
references
References 61 publications
3
40
0
2
Order By: Relevance
“…Especially after [18], several studies have emerged in the static and dynamic econometric analyses framework for different countries. For instance; [19,20,21,22,23,24] are some of these studies. However, findings from the empirical analysis show that the direction of causality differs from country to country.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Especially after [18], several studies have emerged in the static and dynamic econometric analyses framework for different countries. For instance; [19,20,21,22,23,24] are some of these studies. However, findings from the empirical analysis show that the direction of causality differs from country to country.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Zhou and Li [43] confirmed the presence of the Environmental Kuznets curve (EKC) and growth hypothesis for 33 nations from 1990 to 2016. Can and Korkmaz [44] reported the validation of bidirectional causality between renewable electricity output, as well as renewable energy consumption and economic growth in the case of Bulgaria during the period of 1990-2016. Lee and Jung [45] reported that renewable energy consumption has a significant but negative impact on economic growth.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The empirical analysis shows the presence of a bidirectional causality relationship between the consumption of renewable energy and economic growth. This empirical evidence is consistent with current studies such as Kahia et al [72] for Middle East and North African (MENA) countries; Rafindadi and Ozturk [11] for Germany; Koçak and Şarkgüneşi [26] for Albania, Georgia, and Romania; Apergis and Payne [22] for Central American countries; Apergis and Payne [20] for 20 OECD countries; Lin and Moubarak [27] for China; Shahbaz et al [28] for Pakistan; Pao and Fu [53] for Brazil; Marinaş et al [48] for European economies; and Can and Korkmaz [44] for Bulgaria. Economic growth causes capital.…”
Section: Cross-sectional Dependence and Panel Unit Root Analysismentioning
confidence: 99%
“…This Malaysian study revealed that renewable energy have a positive and significant effect on economic well-being both in the short and long run. Can and Korkmaz (2018) focused on Bulgaria to in investigating the relationship between renewable energy consumption and economic growth. The finding from the ARDL model showed no existence of a long run relationship but Toda-Yamamoto causality results posited that renewable energy consumption and renewable electricity output causes economic growth.…”
Section: Literature Reviewmentioning
confidence: 99%